ATP‐binding cassette transporter 1 (ABCA1) deficiency decreases platelet reactivity and reduces thromboxane A2 production independently of hematopoietic ABCA1. (17th February 2016) - Lhermusier, T.; Severin, S.; Van Rothem, J.; Garcia, C.; Bertrand‐Michel, J.; Le Faouder, P.; Hechler, B.; Broccardo, C.; Couvert, P.; Chimini, G.; Sié, P.; Payrastre, B.
Abstract : Essentials The role of ATP‐binding cassette transporter 1 (ABCA1) in platelet functions is poorly characterized. We studied the impact of ABCA1 deficiency on platelet responses in a mouse model and two Tangier patients. ABCA1‐deficient platelets exhibit reduced positive feedback loop mechanisms. This reduced reactivity is dependent on external environment and independent of hematopoietic ABCA1. Summary: Background: The ATP‐binding cassette transporter ABCA1 is required for the conversion of apolipoprotein A‐1 to high‐density lipoprotein (HDL), and its defect causes Tangier disease, a rare disorder characterized by an absence of HDL and accumulation of cholesterol in peripheral tissues. The role of ABCA1 in platelet functions remains poorly characterized. Objective: To determine the role of ABCA1 in platelet functions and to clarify controversies concerning its implication in processes as fundamental as platelet phosphatidylserine exposure and control of platelet membrane lipid composition. Methods and results: We studied the impact of ABCA1 deficiency on platelet responses in a mouse model and in two Tangier patients. We show that platelets in ABCA1‐deficient mice are slightly larger in size and exhibit aggregation and secretion defects in response to low concentrations of thrombin and collagen. These platelets have normal cholesterol and major phospholipid composition, granule morphology, or calcium‐induced phosphatidylserine exposure. Interestingly, ABCA1‐deficient platelets display a reduction in positive feedback loop mechanisms, particularly in thromboxane A2 (TXA2) production. Hematopoietic chimera mice demonstrated that defective eicosanoids production, particularly TXA2, was primarily dependent on external environment and not on the hematopoietic ABCA1. Decreased aggregation and production of TXA2 and eicosanoids were also observed in platelets from Tangier patients. Conclusions: Absence of ABCA1 and low HDL level induce reduction of platelet reactivity by decreasing positive feedback loops, particularly TXA2 production through a hematopoietic ABCA1‐independent mechanism.